Involvement of Indoleamine 2,3-Dioxygenase in Impairing Tumor-Infiltrating CD8+ T-Cell Functions in Esophageal Squamous Cell Carcinoma - Ge Zhang; Wan-Li Liu; Lin Zhang; Jun-Ye Wang; Miao-Huan Kuang; Peng Liu; Yue-Hao Lin; Shu-Qin Dai; Jun Du (Clinical and Developmental Immunology)
The indoleamine 2,3-dioxygenase-(IDO-) mediated microenvironment plays an important role in tumor immune escape. However, the inhibitory effects of IDO on the CD8+ tumour-infiltrating lymphocytes (CD8+ TILs) in esophageal squamous cell carcinoma (ESCC) have not been clarified yet. Here, we found that the level of IDO expression in ESCC tumor specimens correlated with a reduction in the number of CD8+ TILs. Patients with high IDO expression and a low number of CD8+ TILs had significantly impaired overall survival time. IDO expression and functional enzyme activity in ESCC cell lines could be induced by IFNγ. When exposed to the milieu generated by IDO-expressing Eca109 cells, the CD8+ TILs were suppressed in proliferation, and their cytolytic functions against target tumor cells were lost. These results suggested that impairing CD8+ TIL functions by IDO expressed in ESCC possibly contributed to the finding that patients with higher IDO expression have more aggressive disease progression and shorter overall survival time.